Penguatan Gugatan Citizen Lawsuit/Action Popularis sebagai Upaya Perlindungan Hak Konstitusional atas Jaminan Penegakan Hak-Hak Konstitusional Warga Negara terhadap Perbuatan Melawan Hukum oleh Negara - Derry Angling Kesuma (Penerbit Goodwood, 2023)
Purpose: Citizen Lawsuit or Citizen Lawsuit against State officials is actually not known in the Civil Law legal system as applied in Indonesia. Citizen Lawsuit itself was born in countries that adhere to the Common Law legal system. Methodology: Citizen Lawsuit can be applied as the basis for filing a lawsuit against the law contained in the preamble of the constitution or the 1945 Constitution as a guaranteed basic right, from a number of arrangements regarding human rights (HAM), through the Law of the Republic of Indonesia No. 39 of 1999 concerning Human Rights, and in the realm of administrative law, namely the Law of the Republic of Indonesia concerning Consumer Protection No. 8 of 1999. However, these arrangements are not explicitly regulated. For its application in the judiciary, Law No. 48 of 2009, on Judicial Power, states that judges may not refuse to handle cases. The laws and regulations previously described have been widely used by citizens in filing Citizen Lawsuits in Indonesia so far.. Results: The concept of a Democratic state adopted by Indonesia, regarding sovereignty in the hands of the people, according to the author can be implemented properly by streamlining so that the concept of Citizen Lawsuit, because it is in accordance with the objectives of law in Indonesia, especially equal rights before the law between the State and Citizens.